The Influence of Village Expenditure on the Performance of Village Development in All Indonesian Districts - Fransiska Baso; Jamaluddin (ADPEBI, 2024)
In 2014, the Indonesian government formalized Law Number 6 of 2014, which focused on village Management. Its primary goal was to support rapid and sustainable growth in rural areas. This study aims to analyze the impact of village expenditure on the development performance of villages across all districts in Indonesia. The method used is quantitative, utilizing data from 416 districts in Indonesia collected from local governments during the 2018–2021 period, with a total of 1,632 observations in the final sample. The findings of this study indicate that village expenditure significantly influences the improvement of village development performance. These results suggest that an increase in village expenditure tends to positively boost development at the village level, as reflected in the Village Development Index (VDI). The significance of this research lies in its contribution to improving development policy at the village level, where the government is increasingly focused on sustainable and inclusive development. Therefore, the implications of this research can provide valuable insights for policymakers, researchers, and practitioners in the field of community development. By understanding the impact of village expenditure on VDI, the government can optimize budget allocation and enhance the effectiveness of development programs at the village level.